International Capital Mobility and Financial Fragility - Part 4. Which Structural Policies Stabilise Capital Flows When Investors Suddenly Change Their Mind? Evidence from Bilateral Bank Data - Ahrend, Rudiger (OECD Publishing, 2012)
The global financial crisis of 2007-09 and the ensuing sovereign debt crisis in Europe provide evidence that portfolio rebalancing of financial investors can contribute to spread financial turmoil across countries. Rebalancing of portfolios, in turn, may be driven by the need to meet liquidity or capital requirements, or by sudden changes in investor sentiment. This paper tests explicitly for the change-insentiment channel of financial contagion. Using bilateral bank data and an instrumental variables technique that allows focusing on changes in investors' country assessments that are unrelated to fundamentals, changes in investor sentiment are indeed found to drive capital flows. Sentiment-driven capital flows are found to be smaller in countries with a tougher regulatory stance, such as stricter banking supervision or enhanced financial transparency
Keywords: Economics